2019
DOI: 10.1177/0300060519845488
|View full text |Cite
|
Sign up to set email alerts
|

Virus-induced pathogenesis, vaccine development, and diagnosis of novel H7N9 avian influenza A virus in humans: a systemic literature review

Abstract: H7N9 avian influenza virus (AIV) caused human infections in 2013 in China. Phylogenetic analyses indicate that H7N9 AIV is a novel reassortant strain with pandemic potential. We conducted a systemic review regarding virus-induced pathogenesis, vaccine development, and diagnosis of H7N9 AIV infection in humans. We followed PRISMA guidelines and searched PubMed, Web of Science, and Google Scholar to identify relevant articles published between January 2013 and December 2018. Pathogenesis data indicated that H7N9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 159 publications
(317 reference statements)
0
7
0
Order By: Relevance
“…As a result, at least some aspects of virus evolution and emergence are repeatable and predictable [24]. Additionally, since the HA protein is the primary target of neutralizing antibodies [50] and determines specificity for efficient virus transmission between individuals and between species [51], parallel/convergent evolution on HA could not only alter the receptor binding affinity but also affect antigenicity. In this study, we found several parallel/convergent mutations on HA1, including four in the RBS (125 in 130-loop, 151 in 150-loop, 177 in 190-helix, and 217 in 220-loop).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, at least some aspects of virus evolution and emergence are repeatable and predictable [24]. Additionally, since the HA protein is the primary target of neutralizing antibodies [50] and determines specificity for efficient virus transmission between individuals and between species [51], parallel/convergent evolution on HA could not only alter the receptor binding affinity but also affect antigenicity. In this study, we found several parallel/convergent mutations on HA1, including four in the RBS (125 in 130-loop, 151 in 150-loop, 177 in 190-helix, and 217 in 220-loop).…”
Section: Discussionmentioning
confidence: 99%
“…There have been 5 documented H7N9 outbreaks in China from 2013 to 2017, but human-tohuman transmission was only evident to some extent in the last outbreak (32)(33)(34), consistent with a Vx that is not yet humanized and likely to cause far fewer cases than other respiratory pathogens. However, considering the estimated CFR for H7N9 patients is ~30% (30,34), even if only 10% of the COVID-19 patients in Wuhan also had H7N9 it would explain the high CFR initially reported in China.…”
Section: Empirical Evidence For a Potential Vx In The Wuhan Outbreakmentioning
confidence: 95%
“…Of note, H7N9 infections in humans are described as indistinguishable from the 2003 definition of SARS (27)(28)(29), causing fever, hypenia, long-term damage to lung and cardiac tissue in recovered patients, and high mortality rate. Moreover, H7N9 viruses can be antigenically and genetically very different from common fluA strains (e.g H1N1), making them undetectable by standard flu tests and likely to go undiagnosed in hospital settings (30)(31).…”
Section: Empirical Evidence For a Potential Vx In The Wuhan Outbreakmentioning
confidence: 99%
“…There have been 5 documented H7N9 outbreaks in China from 2013 to 2017, but human-tohuman transmission was only evident to some extent in the last outbreak (32)(33)(34), consistent with a Vx-like pathogen that is not yet humanized and likely to cause far fewer cases than other respiratory pathogens. However, considering the estimated CFR for H7N9 patients is ~30% (30,34), even a small proportion of COVID-19 patients that also have Vx (or specifically H7N9), could explain the high CFR reported in some regions/periods, i.e Wuhan in February, Lombardi in March/April, and later in NYC.…”
Section: Empirical Evidence For a Potential Vx In The Wuhan Outbreakmentioning
confidence: 99%